2019
DOI: 10.1371/journal.pone.0204187
|View full text |Cite
|
Sign up to set email alerts
|

Involving patients and the public in medical and health care research studies: An exploratory survey on participant recruiting and representativeness from the perspective of study authors

Abstract: Research on patient and public involvement so far concentrates on defining involvement, describing its methods, and analyzing involvement practices in various individual research disciplines. There is little empirical data on the process of and aims for selecting (lay) PPI participants, and to what extend they can and should be representative of the population at large. To explore practices and perceptions on these issues and on future PPI conduct more generally, we sent an electronic survey to authors who pub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…Across Europe, awareness of the benefits of patient and public involvement (PPI) in health care research is rapidly increasing [10]. Lander et al [11] has identified a number of benefits of actively engaging with service users, including the development of research goals that are congruent with those of the public and “assessing the impact and value of health technologies and health services.” However, there remains wide variation among countries in the opportunities to do so [10]. In the United Kingdom, PPI in research refers to researchers and patients, carers, and the public working in collaborative partnership to add value to the research process in an accessible and meaningful way [12].…”
Section: Introductionmentioning
confidence: 99%
“…Across Europe, awareness of the benefits of patient and public involvement (PPI) in health care research is rapidly increasing [10]. Lander et al [11] has identified a number of benefits of actively engaging with service users, including the development of research goals that are congruent with those of the public and “assessing the impact and value of health technologies and health services.” However, there remains wide variation among countries in the opportunities to do so [10]. In the United Kingdom, PPI in research refers to researchers and patients, carers, and the public working in collaborative partnership to add value to the research process in an accessible and meaningful way [12].…”
Section: Introductionmentioning
confidence: 99%
“…Involving more than one person increases the breadth of experience to the project, allows those involved to support and encourage each other, and allows for multiple perspectives. PI members cannot be representative of everyone who has a specific condition [23,24]. Having a PI team is beneficial to allow for wider diversity and experiences.…”
Section: Public Involvement and Patient-reported Outcome Measuresmentioning
confidence: 99%
“…As a consequence, the involved patients did not represent the entire future target group for the feedback intervention. 68 When checking the comprehensibility and acceptance of the two feedbacks, five out of nine participants took part in at least one of the previous workshops. Because they already commented on content-, language-and design-related aspects of the feedback, their initial reaction may have been biased.…”
Section: Strengths and Limitationsmentioning
confidence: 99%